Pathogenic treatment of the inflammatory diseases of the urogenital tract in women of reproductive age - O.I. Letyaieva; O.R. Ziganshin (LCC «Medicine-Inform», 2021)
O.I. Letyaeva, O.R. Ziganshin South Ural State Medical University, Chelyabinsk, Russian Federation This paper discusses one of the important gynecological issues, inflammatory diseases of the urogenital tract caused by opportunistic microbes. The treatment and long-term control over these conditions are challenging and depend on their occurrence and high risk of complications. Impaired local anti-infectious protection is one of the risk factors of chronic inflammation. Since the disease may recur even after successful treatment, domestic and foreign authors increasingly focus on immunotherapy as a part of complex strategy and isolated entity. Local immunotherapy may prevent recurrences and activate host defense. This paper describes the management of two women with mixed infections. The first woman with chronic recurrent inflammation (cervicitis caused by U. urealyticum, vulvovaginal candidiasis, and aerobic vaginitis) in whom prior etiological therapy was ineffective received immunotherapy which resulted in long-term remission. The second woman with coexistent papillomavirus infection (genital warts) and bacterial vaginosis received immunotherapy and topical etiological treatment. As a result, clinical symptoms, the size and number of genital warts reduced which greatly facilitated their chemical destruction. Keywords: genital tract, urogenital infections, papillomavirus infection, bacterial vaginosis, local immunity, biofilms. For citation: Letyaeva O.I., Ziganshin O.R. Pathogenic treatment of the inflammatory diseases of the urogenital tract in women of reproductive age. Russian Journal of Woman and Child Health. 2021;4(1):59-64. DOI: 10.32364/2618-8430-2021-4-1-59-64.